Carbon nitride based materials for heterogeneous photocatalysis - Khan, MA (2016)
Photocatalysis on semiconductor surfaces has grown tremendously in the last four decades. One reason for this is its analogy with photosynthesis, the most important natural photochemical process. Semiconductors to some extent can mimic the key steps of this fascinating heterogeneous photocatalytic process, i.e., photochemical charge generation, charge trapping, interfacial electron exchange and subsequent reaction. Building on this premise this thesis constitutes an investigation into the photocatalytic properties and applications of semiconducting layered framework carbon nitride based materials. Similar to traditional photocatalysts, the photocatalytic activity and efficiency of carbon nitride systems developed thus far is limited mainly by the fast recombination and low mobility of photogenerated excitons. Here, by exploiting the band alignment strategy, carbon nitride isotype (type II) and carbon nitride-niobium oxide of type II semiconductor heterojunctions were successfully constructed with the aim of suppressing the exciton recombination and improving charge extraction for the successful initiation of desirable redox chemistry. These features were demonstrated by employing the materials in heterogeneous photocatalysis for water splitting, organic pollutant decomposition and photochemical organic synthesis. Carbon nitride isotype heterojunctions constructed by controlled thermal condensation are shown to exhibit lower recombination of excitons relative to the pristine carbon nitride. As a consequence photocurrent generation and visible light driven H2 production activity was enhanced. This increase is attributed to the surface passivation and improved electron mobility of built-in electric field which arises from the topology-induced band offset of favoured type II heterojunction configuration. Building on the insights into the heterojunction-activity dependence, new type II graphitic carbon nitride (C3N4), Nb2O5 (C3N4-Nb2O5), heterojunctions synthesised via a hydrothermal method were exploited for their photodegradation ability of the organic pollutants. The synergic effect of carbon nitride and Nb2O5 coupling leads to the substantial photocatalytic activity improvement which can be attributed to the formation of an intimate interface and gradual attenuation of energy-wasteful charge recombination processes in C3N4-Nb2O5 heterojunctions materials. While water splitting and pollutant decomposition using semiconductors has received the bulk of attention, the possibilities concerning chemical synthesis are only beginning to be meaningfully exploited. We, therefore, employed carbon nitride to catalyse photo organic synthesis. It was demonstrated for the first time that carbon nitride can efficiently catalyse the photoacetalization reactions of aldehydes/ketones with alcohols, forming acetals at high yields using visible light under ambient conditions. Mechanistic studies suggest that the transient charge separation at the surface of this material is sufficient to catalyse the reaction in the absence of Lewis or Brønsted acids or solvent systems. Since the photoacetalization of aldehydes occurs under conditions similar to those of alcohols oxidation, both using visible light and carbon nitride as a catalyst, the two reactions actually proceed via different mechanisms. This study also demonstrates, visible light induced heterogeneous auto-tandem catalysis, coupling the oxidation and subsequent acetalization of alcohols in a single chemical process. This green strategy can be applicable to a wide variety of organic photo-induced synthesis.